2019
DOI: 10.4103/jcd.jcd_31_19
|View full text |Cite
|
Sign up to set email alerts
|

The marginal discrepancy of lithium disilicate onlays: Computer-aided design versus press

Abstract: Aim:The aim of the study was to evaluate and compare the vertical marginal discrepancy of computer-aided design (CAD)/computer-aided manufacturing (CAM) and pressable lithium disilicate onlays.Materials and Methods:A maxillary first premolar typodont tooth was prepared to receive lithium disilicate onlay. Mesio-occluso-distal cavity was prepared with palatal cusp reduction and collar preparation. In the proximal box, gingival seat was placed 1 mm coronal to the cementoenamel junction and mesiodistal width of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Lithium disilicate ceramic is generally superior to CAD/CAM polymer-based materials in terms of flexural strength, abrasion resistance, and marginal/material discolorations. 19,20,24,25,26 These results…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Lithium disilicate ceramic is generally superior to CAD/CAM polymer-based materials in terms of flexural strength, abrasion resistance, and marginal/material discolorations. 19,20,24,25,26 These results…”
Section: Discussionmentioning
confidence: 51%
“…CAD/CAM can be used to fabricate not only silicate ceramics (such as lithium disilicate) but also zirconia, polymer‐infiltrated ceramics, or various polymer‐based materials 19,20 . They can be used for various indications, including with manual veneering for superior esthetical outcomes 19,20 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were very few in vivo studies included [ 27 , 31 , 34 , 36 ], of which, only one was carried out as a randomised controlled trial with the lowest risk of bias [ 27 ]. The results from the studies using models rather than real teeth will inherently produce differing results.…”
Section: Discussionmentioning
confidence: 99%
“…compared the marginal fit between CAD-CAM and hot-press lithium disilicate crowns and concluded that the marginal fit of crowns fabricated by CAD-CAM technique was better than by pressed technique. [ 13 14 ] Therefore, in the current study CAD-CAM technique of fabrication was employed.…”
Section: Discussionmentioning
confidence: 99%